1994
DOI: 10.2134/agronj1994.00021962008600020016x
|View full text |Cite
|
Sign up to set email alerts
|

Variability among Soybean Genotypes in Response to Nodulation by a Rhizobitoxine‐Producing Strain of Bradyrhizobia

Abstract: Nodulation by rhizobitoxine‐producing (RT+) strains of Bradyrhizobium elkanii (syn. Bradyrhizobium japonicum; DNA homology group II) has been shown to reduce shoot growth, N2 fixation, and seed yield of ‘Forrest’ soybean (Glycine max [L.] Merr.). We conducted greenhouse and field experiments to assess the frequency of these negative responses among selected soybean cultivars. In the greenhouse, 38 cultivars representing a range of yield potentials, maturity groups, and growth habits were inoculated with B. elk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…The observed significantly better performance of PGCP-4 and PGCP-6, show variable differences in the physiological structures, which made these cultivars readily able to absorb nutrients and water from the soil, and to effectively carry out the photosynthetic process and ultimately, to accumulate the higher amount of photosynthates. This observation was in congruence with the earlier reports of Fuhrmann and Vasilas (1994), which concluded that the cultivars respond differently to various environmental factors, and this differential response is primarily driven by their genetic makeup and their adaptive capabilities. The dehydrogenase activity is linked with the microbial activity, related with the physiological efficiency of microorganisms associated with plants, which is mainly host-dependent as they releases nutrients for microbes in the form of root exudates.…”
Section: Resultssupporting
confidence: 91%
“…The observed significantly better performance of PGCP-4 and PGCP-6, show variable differences in the physiological structures, which made these cultivars readily able to absorb nutrients and water from the soil, and to effectively carry out the photosynthetic process and ultimately, to accumulate the higher amount of photosynthates. This observation was in congruence with the earlier reports of Fuhrmann and Vasilas (1994), which concluded that the cultivars respond differently to various environmental factors, and this differential response is primarily driven by their genetic makeup and their adaptive capabilities. The dehydrogenase activity is linked with the microbial activity, related with the physiological efficiency of microorganisms associated with plants, which is mainly host-dependent as they releases nutrients for microbes in the form of root exudates.…”
Section: Resultssupporting
confidence: 91%
“…The degree of susceptibility in their study ranged from highly resistant to highly susceptible. Fuhrmann and Vasilas (1994) also showed variability among soybean genotypes in response to RT. They evaluated 38 soybean cultivars in the greenhouse for their response to RT and reported that cultivars ranged from tolerant to very sensitive.…”
Section: Introductionmentioning
confidence: 92%